Caracterização florística, diversidade e correlação ambiental na Floresta Nacional de São Francisco de Paula, RS - Kanieski, Maria Raquel (2010)
Populations and species are disappearing due to disturbances in the environment caused by human activities. Given the obvious risk of loss of diversity, it is increasingly necessary to take actions concerning preservation, in which safety features are necessary for measuring the variation of diversity in space and time. The aim of this study was to evaluate the structure and diversity in the arboreal component and natural regeneration in an area of Araucaria forest in the National Forest of São Francisco de Paula, RS. The vegetation sampling was performed by analyzing 180 subunits of 10m x 10m, where all the arboreal individuals and natural regeneration were inventoried. The parameters of frequency and density, dispersion indexes of MacGuinnes, Fracker and Brischle and Payandeh, and different alpha and beta indexes of diversity were calculated. The values of alpha indices were correlated with environmental variables by Canonical Correspondence Analysis (CCA). It was found 102 species, distributed in 66 genera and 36 families. The dispersion indexes showed different patterns for the arboreal component and natural regeneration. The Margalef, Shannon, and the Beta indexes were underestimated, possibly influenced by the size of sample unit. Index Menhinick represented the diversity in a very real form, even in small sampling units. The indexes of Simpson and Mcintosh denote low dominance and the equity indexes showed high uniformity in species. The CCA showed that diversity is strongly related to declive, stoniness and contents of sand and clay, in the arboreal component, and contents of clay, fine sand and silt, in natural regeneration.